THE EFFECT OF WORKLOAD, JOB SATISFACTION AND JOB STRESS ON EMPLOYEES' TURNOVER INTENTION PT. SURYAMAS CIPTA SENTOSA SURABAYA - Pranoto, Eko Adi; Miradji, Mohammad Afrizal; Estiasih, Soffia Pudji (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2024)
Human resources are a very crucial asset for a company. How well the resources are managed will determine the success of the Company in the future. Companies need healthy and motivated human resources to become more advanced, develop and survive in a changing business environment. The purpose of this study is how the influence of turnover intention on workload, job satisfaction and work stress on employees of PT. Suryamas Cipta Sentosa Surabaya. Quantitative research methods are one of those used. The population of the study was 124 and a sample of 75 respondents was used as a sample, namely as participants. The sample was taken using a purposive sampling technique. Instruments testing, hypothesis testing, multiple linear regressions analysis, and classical assumptions testing through the SPSS version 22 application are some of the data analysis methodology. The results of the study showed that the variables of workload, job satisfactions and work stress partially had a positive and significant effect on turnover intention on employees of PT. Suryamas Cipta Sentosa Surabaya. Then workload, job satisfactions and stress simultaneously had a positive and significant effect on turnover intention on employees of PT. Suryamas Cipta Sentosa Surabaya. Keywords: Workload, job satisfaction, job stress and turnover intention